Oleanolic acid arrests cell cycle and induces apoptosis via ROS‐mediated mitochondrial depolarization and lysosomal membrane permeabilization in human pancreatic cancer cells. Issue 8 (8th June 2012) - Wei, Jianteng; Liu, Ming; Liu, Haizhou; Wang, Hui; Wang, Fengxia; Zhang, Yuyan; Han, Lijun; Lin, Xiukun
ABSTRACT Oleanolic acid (OA), a pentacyclic triterpenoid, exhibits potential anti‐tumor activity against many tumor cell lines. This study aims to examine the anti‐tumor activity of OA on pancreatic cancer cells and its potential molecular mechanism. The results showed that the proliferation of Panc‐28 cells was inhibited by OA in a concentration‐dependent manner, with an IC50 (The half maximal inhibitory concentration) value of 46.35 µg ml−1, as determined by MTT (3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) assay. The cell cycle was arrested in S phase and G2/M phase by OA. The study also showed that OA could induce remarkable apoptosis, evidenced by an increased percentage of early/late apoptotic cells, DNA ladder and nuclear morphology change. Further study revealed that OA could induce Reactive Oxygen Species (ROS) generation, mitochondrial depolarization, release of cytochrome C, lysosomal membrane permeabilization and leakage of cathepin B. The expression of apoptosis‐correlated proteins was also affected in cells treated with OA, including activation of caspases‐3/9 and cleavage of PARP. Further study confirmed that ROS scavenger vitamin C could reverse the apoptosis induced by OA in Panc‐28 cells. Our results provide evidence that OA arrests the cell cycle and induces apoptosis, possibly via ROS‐mediated mitochondrial and a lysosomal pathway in Panc‐28 cells. Copyright © 2012 John Wiley & Sons, Ltd.